2014 IEEE/ACM 7th International Conference on Utility and Cloud Computing 2014
DOI: 10.1109/ucc.2014.33
|View full text |Cite
|
Sign up to set email alerts
|

Role-Based Templates for Cloud Monitoring

Abstract: Cloud computing has evolved in the recent years to a well established computing paradigm. With this evolution, the complexity and requirements for monitoring cloud-based services have also increased. Without a doubt, monitoring for cloud computing is a crucial task which has been addressed in a number of research works. However, monitoring for cloud computing is often designed to be carried out by cloud providers. Monitoring by cloud providers on the one hand offers the flexibility and full control required fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
2
2
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…In spite of above-indicated monitoring challenges, Cloud monitoring tools are mainly implemented by the CSPs which makes the trustworthiness of the monitoring data questionable [84]. Amazon CloudWatch [3], Google Stackdriver Monitoring [35] are examples of such monitoring systems.…”
Section: Cloud Monitoring and Its Challengesmentioning
confidence: 99%
See 1 more Smart Citation
“…In spite of above-indicated monitoring challenges, Cloud monitoring tools are mainly implemented by the CSPs which makes the trustworthiness of the monitoring data questionable [84]. Amazon CloudWatch [3], Google Stackdriver Monitoring [35] are examples of such monitoring systems.…”
Section: Cloud Monitoring and Its Challengesmentioning
confidence: 99%
“…In fact, full access to all resources (e.g., bare-metal servers, networking components, cloud management platforms, virtualisation tools, etc.) is required to deploy holistic monitoring solutions [84], and such access is only available to the CSP. While the full control over monitoring systems and generated logs allow a CSP to monitor and maintain Cloud services efficiently, it gives them a controversial power over evidential resources that are significantly important to CSCs.…”
Section: Introductionmentioning
confidence: 99%
“…Implementation of a complete monitoring system requires full access to the components that will be monitored [30]. Nguyen et al [30] indicated that only Cloud providers have such level of access to Cloud resources. Therefore, most of the Cloud monitoring solutions are built by Cloud providers.…”
Section: Examples Of Solved Challengesmentioning
confidence: 99%
“…In contrast, Cloud consumers require full details of monitoring data and need a way to verify the monitoring details that are provided by the Cloud provider. To address this issue, Nguyen et al [30] combined role-based monitoring templates with agent-based monitoring and used event processing engine to refine the collected data and to provide a trustworthy and holistic monitoring solution.…”
Section: Examples Of Solved Challengesmentioning
confidence: 99%
See 1 more Smart Citation